Pembingkaian Sebagai Sikap Etis terhadap Tiga Problem Yang Ditimbulkan Bioteknologi - Yeremias Jena (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2017)
Biotechnology is the biological child of science and technology. As an important part of the application of technology in the area of biology, a wide area of biotechnology extends from various living systems to organisms. As an applied field of science and technology, it emerges as a discipline that seeks to develop or produce various outcomes or applications by utilizing various biological systems, living organisms and their derivatives, creating and / or modifying things for specific purposes. The latter mentioned refers to the efforts of scientists and technology developers to create a better and more prosperous human life. Since its rapid and aggressive development in the 1970s, biotechnology has been positioned as a discipline capable of overcoming various human problems, whether it is food limitations, fighting various diseases, manipulating population growth, or creating applications to detect crime. Biotechnology brings many benefits to human life, but skepticism and ethical criticism are still needed. Instead of naively rejecting the progress of science and technology, one way to submit criticism that can be accepted by scientists is to examine the progress of biotechnology itself before showing its weaknesses. This is done by a group of ethicists in science and technology who are members of the Nuffield Council on Bioethics (NCB). They found - among other things - that the development of biotechnology turned out to leave problems that were difficult to solve even by the scientists themselves. Three main problems are shown in this paper, namely the problem of uncertainty, ambiguity, and the potential for transformation. The disclosure of these three problems does make us aware of not accepting biotechnology naively. But more than that, we are made aware of having certain ethical attitudes towards the development of biotechnology. The framing offered in this paper can be seen as a contribution to ethical and bioethical studies in dealing with the three problems that biotechnology poses.